ANALISIS NILAI MORAL DALAMNOVEL IBUKU PEREMPUAN BERWAJAH SURGA KARYA NOVANKA RAJA - Sudirman Shomary, Sudirman; Roziah, Roziah; Susanti, Rika Rema (Perspektif, 2014)
Many literary works have benefits for human life, because literature is born of human life that contains the values that can be used by the man himself as a rule in life. Those values are one of which is a moral value. The problem in this study can be formulated as follows: (1) What is the moral value associated with the responsibilities of the novel IBUKU PEREMPUAN BERWAJAH SURGA”by Novanka Raja ?, (2) How is the value associated with the moral conscience of the novel IBUKU PEREMPUAN BERWAJAH SURGA”by Novanka Raja ? (3) What is the moral values relating to liability in the novel IBUKU PEREMPUAN BERWAJAH SURGA”by Novanka Raja ?. The study aims to describe, analyze and interpret the moral values contained in the novel IBUKU PEREMPUAN BERWAJAH SURGA”by Novanka Raja. The theory is used to analyze the problem of this research is the theory put forward by Burhanuddin Salam (2000). The approach used in this study is a qualitative approach, the author presents the data by considering the aspects of quality and quality were studied. The data collection technique was performed using the technique hermeneutic, record and summarize. The method used was descriptive, namely in the form of data description and analysis. This type of research is the research library (library research). Results of research conducted showed that the novel IBUKU PEREMPUAN BERWAJAH SURGA”by Novanka Raja there is the moral value associated with (1) The responsibility can be seen through a character named Risma against himself, and his daughters, Rima, which is based on the awareness, love or joy , and courage. (2) Conscience seen Risma darisikap reflected in accepting the situation with a sincere heart. (3) The obligation can be seen through yourself, man to God, from parents to children and children to parents.